The digital market for local services: a one-night stand for workers? An example from the on-demand economy - de Groen, Willem Pieter; Maselli, Ilaria; Fabo, Brian (Brussels, 2016)
"This case study provides a snapshot of the dynamics in the digital market for locally provided personal services. Based on a case study for a Belgium platform with 14,113 identified workers and 9,459 posted tasks, the findings suggest that the current intermediation is inefficient. Only a limited share of the tasks posted on the platform are being completed, whereas the characteristics of the not-completed tasks are fairly limited. Moreover, just a small share of the workers participating in the platform is actually performing the completed tasks. Their average earnings per hour are in most cases above the minimum wage and even above the median wage in the offline market. At the present time, however, the limited earnings for individual workers prevent this mode of working from becoming an alternative to a conventional job. In addition to the standard determinants of workers’ earnings (e.g. gender, age, occupation, etc.), the characteristics and evaluation mechanism of the platform have a large influence on the distribution of tasks and earnings."